Fördern und fordern in der Wohnungspolitik: Wissenschaft und Praxis im Dissens über stille Reserven von Wohnungsbaugenossenschaften - Michael Braun Alexander (IBF - Institut für Bank- und Finanzgeschichte e.V., 2024)
Public housing policy has given housing cooperatives above-average market shares, in some cases. This was achieved despite the fact that the sponsor, believing that he was doing good, even temporarily slowed down the independent development of his target. The case study of Hochtaunusbau shows that public funding can be at the expense of the cooperatives. The public sponsor, in this case the city, also prevented market-based incentive systems, such as dividends. The cooperative saw this as a brake on its equity formation. After all, the good location, close to the Taunus and close to the financial center of Frankfurt am Main, has led to high hidden reserves. The cooperative can hardly make use of this, either to give members a greater share in the cooperative's profits or to offer more members an apartment through new construction. It essentially saw itself as a portfolio holder. Evidence from the science of cooperatives, according to which the reserves of a cooperative can certainly be divided, is not accepted in practice. And public sponsors continue to provide funds. They do not demand that cooperatives use their hidden reserves for the cooperative purpose.
Keywords: D22; L85; N94; P13; R38; 330